The neglected association between central obesity markers and abdominal aortic aneurysm presence: A systematic review and meta-analysis - Sheng, Chang; Liu, Tinghua; Chen, Shen; Liao, Mingmei; Yang, Pu (Frontiers in Cardiovascular Medicine, 2023)
Purpose: To review the association between central obesity and abdominal aortic aneurysm (AAA). Methods: The PubMed, Web of Sciences, Embase, Cochrane Library, and The China national knowledge infrastructure (CNKI) were searched up to April 30, 2022. Studies investigating the association between markers of central obesity and AAA were included. The included studies had to use a recognized measure of central obesity, namely waist circumference (WC) and waist-to-hip ratio (WHR) or employ imaging techniques to quantify the abdominal adipose distribution, including ultrasound scan or computed tomography (CT) imaging results to establish the presence or absence of AAA. Results: Eleven clinical studies were identified of which eight discussed the association between physical examination and AAA, and three studies mainly focused on abdominal fat volume. Seven studies reported a significant positive association between markers of central obesity and AAA presence. Three studies did not find any significant association between markers of central obesity and AAA. One of the remaining studies reported different results for each sex. Three studies pooled in a meta-analysis identified correlation between central obesity and AAA presence (RR =1.29; 95% confidence interval, 1.14–1.46). Conclusion: Central obesity plays a role in the risk of AAA. Standardized central obesity markers may be predictors of AAA. However, there was no association between abdominal fat volume and AAA. Additional relevant evidence and specific mechanisms warrant further study.